Stable Long‐Term Cycling of Room‐Temperature Sodium‐Sulfur Batteries Based on Non‐Complex Sulfurised Polyacrylonitrile Cathodes - Blázquez Moreno, Jesús M. (2024)
The cost-effectiveness and high theoretical energy density make room-temperature sodium-sulfur batteries (RT Na–S batteries) an attractive technology for large-scale applications. However, these batteries suffer from slow kinetics and polysulfide dissolution, resulting in poor electrochemical performance. Thus, the sulfurised polyacrylonitrile (SPAN) cathode is postulated as a suitable material due to the retention of sulfur through covalent bonds and the increase in the conductivity of sulfur. Furthermore, in this work the synthesis of SPAN has been carried out using simple synthesis methods, making it scalable, economical, and without the use of toxic compounds. The incorporation of the SPAN material helps mitigate the shuttle effect, reducing the capacity loss and improving both the efficiency and lifespan of Na–S batteries. The SPAN-based cathode demonstrates that this RT Na–S battery configuration shows high stability, reaching 1000 cycles with a capacity loss per cycle of 0.11% and a satisfactory specific capacity of 400 mAh/gs at a high rate of 2C. This study demonstrates that the utilisation of SPAN derived from a non-complex synthesis can be a viable alternative for enhancing the future of Na–S batteries technology.